Clinical Profile and Treatment Outcomes in Patient with Acromegaly Using 14th Acromegaly Consensus Criteria - Jyoti Sharma; Rajeev Kasaliwal; Puneet Shivnani; Utkarsh Balani; Payal Bargujar; Pankaj Gupta; Bhawani S. Sharma; Vineet Mishra; Akash Mishra; Surendra K. Sharma (Indian Journal of Endocrinology and Metabolism)
Introduction: Acromegaly is a chronic systemic disease characterized by excessive secretion of growth hormone (GH) and insulin-like growth factor 1 (IGF-1). This study reviews our experience with endoscopic transsphenoidal surgery (TSS) in acromegaly patients, focusing on remission rates according to the 2023 consensus criteria. Methods: We conducted a hospital based, retrospective study involving 42 patients diagnosed with acromegaly who underwent endoscopic TSS, between January 2020 and June 2024. Clinical and hormonal profiles, comorbidities and outcome data were analysed. Remission was defined as age-adjusted IGF-1 levels 3 months post-surgery. Results: Mean age at diagnosis was 36.43 ± 10.70 years. The two most frequent presenting symptoms were headache (64.28%) and visual deficits (47.61%). Common comorbidities included diabetes mellitus (23.8%) and hypertension (28.57%). Pre-operative hormonal evaluation revealed secondary hypogonadism in 41.66% of patients, followed by hypothyroidism (23.81%) and cortisol deficiency (21.43%). Biochemical remission was achieved in 18 out of 42 patients (42.85%), including all five patients with microadenomas and 35.13% of those with macroadenomas. Although Knosp grade, maximum tumour diameter and pre-operative post glucose growth hormone levels showed significant associations in univariate analyses, these associations were not significant after adjustment. On multivariate analysis, post-operative day 2 GH levels (≤2.75 ng/ml) emerged as a significant predictor of remission. Conclusions: This study provides the comprehensive review of clinical presentations and outcomes of patients with acromegaly based on the latest acromegaly consensus guidelines. Notably, a post-operative day 2 GH less than 2.75 ng/ml emerged as a significant predictor of outcome.